Why do top predators engage in superpredation? FRom an empirical scenario to a theoretical framework - Lourenço, Rui (2019)
Lethal interactions can shape ecosystem structure, and consequently understanding their causes is ecologically relevant. To improve both empirical and theoretical knowledge on superpredation (i.e. predation on high-order predators), we studied an eagle owl population, including its main prey and mesopredators, and then we crossed these results with existing theories to provide a reasoning framework. We ftted our feld data into four main causes explaining lethal interactions: food stress, opportunistic superpredation, removal of a competitor, and removal of a potential threat. Empirically, superpredation seemed to be mostly determined by the combination of the food-stress and opportunistic-superpredation hypotheses, which highlights the complexity of the factors triggering superpredation. Therefore, besides being a response to lower food availability, superpredation may also represent an eﬀective mechanism to remove potential predators and/or competitors, either intentionally or not. Our theoretical framework focused on the decision-making process in superpredation, considering four inter-related stages: encountering; attacking; and capturing a mesopredator; as well as consuming a mesopredator once killed. Superpredation almost certainly results from a complex process of decision-making, accounting for costs and benefts assessed moment-to-moment and for each mesopredator individual. It is time to build bridges between theoretical and empirical studies to further understand the mechanisms driving complex interactions among top predators and mesopredators.